Optimal conditions for the kinematic analysis in fresh semen of Brahman bulls with a CASA-Mot system - Víquez, Luis Gabriel (2021)
Introduction. The optimal conditions for semen analysis enable us to standardize the evaluation protocols. Objective. To evaluate the effect of external factors related to the semen analysis on the sperm subpopulations of the Brahman cattle. Materials and Methods. The study was conducted with animals from two cattle farms in Alajuela, Costa Rica, from September to December 2019. Ten Brahman bulls were used that were electroejaculated and the semen was diluted with three commercial diluents: Andromed®, Androstar®, and BTS, at two temperatures (37 and 29 °C). The samples were analyzed using a CASA-Mot ISAS®v1 system and ISAS®D4C counting chambers (10, 16 and 20 µm) and Spermtrack® were used at different analysis times (0, 3, 6 and 12 h). Results. The Spermtrack® presented higher curvilinear velocity but lower linearity compared to the other counting chambers (p<0.05). The samples durability was lower for all the sperm kinematic variables (p<0.05), except for the straightness index (STR). Curvilinear velocity was higher when Andromed® was used, but there was greater progressivity with Androstar® (p<0.05). Five sperm subpopulations were identified from three main components: velocity, progressiveness, and undulation. The distribution of spermatozoa in the subpopulations varied (p<0.05) according to sample durability and counting chamber. Conclusion. The type of diluent, dilution temperature, counting chamber, and time elapsed after initial semen loading conditioned ejaculate kinematic variables. Semen motility and kinematics improved when chamber heights of 20 µm and Androstar® diluent were used. The existence of sperm subpopulations in the ejaculate was affected by the type of extender used, which conditioned the presence of different motility patterns, progressiveness and cell undulation in the different subpopulations within the ejaculate.